WRITING PERFORMANCE OF ISLAMIC UNDERGRADUATE STUDENTS IN THE ISSUES OF INTEGRATION TECHNOLOGY AND LANGUAGE LEARNING - Nur Rahmiani (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2020)
This work aims at measuring the performance of students in writing an essay in three critical aspects, namely the material of the writing, comprehension aspect, and student’s feedback. The essay comes from a mid-term writing test for Islamic undergraduate students using content that relates to the student’s field of expertise. The data is analysed using a mixed method that is descriptive quantitative-qualitative. First, the authors utilize a premium online application to notice the extent of correctness, clarity, engagement, delivery, and readability. Second, the author explores information about student’s response to the implications of integration technology in language learning with the Grammarly online as an automatic-evaluation writing performance. The results signify that the issue of correctness mostly appears with an average value of 24.3 or 292 cases in a total of 593 material writing problems. The other hands, the quality of writing based on the readability score shows that most of the writing is more suitable to be read by at least readers with the senior high school levels (10th grade-students). It is in contrast with the level of education who made the essay. Student feedback emphasises the suitability of applying Grammarly in language learning both individually and in a working group. Suggestion for education managements is that every student from various major needs to improve the quality of writing, of course, by involving qualified lecturers and appropriate applications. In the future, the utilization of teaching-learning technology in English writing is needed and strengthened with lecturer guidance.